Production of Lysozyme by Staphylococci and Its Correlation with Three Other Extracellular Substances - Jay, James M. (1966)
Jay, James M. (Wayne State University, Detroit, Mich.). Production of lysozyme by staphylococci and its correlation with three other extracellular substances. J. Bacteriol. 91:1804–1810. 1966.—Lysozyme production was determined on plates containing 1 mg/ml of Lysozyme Substrate in Heart Infusion Agar with incubation at 37 C for 48 hr. Its production was compared with that of α-hemolysin and sheep hemolysin and egg-yolk precipitation, by use of both coagulase-positive and coagulase-negative strains of staphylococci. Of 126 coagulase-positive strains tested, 120 or 95.2% produced lysozyme, 117 or 92.9% produced α-hemolysin, 108 or 85.7% precipitated egg yolk, and 102 or 81% produced sheep hemolysin. Of the 49 coagulase-negative strains (which included 22 pathogens), only 4 or 8.1% produced lysozyme, 14 or 28.6% produced α-hemolysin, 13 or 26.5% produced sheep hemolysins, and 5 or 10.2% precipitated egg yolk. Only two of the six coagulase-positive strains which failed to produce lysozyme showed any consistent patterns in relation to the four characteristics determined. The four coagulase-negative strains which produced lysozyme were inconsistent for the other characteristics measured. It is suggested that lysozyme production is more a property of coagulase-positive staphylococci, and therefore a better ancillary test of pathogenicity, than either production of α-hemolysin or egg-yolk precipitation, because the incidence of lysozyme producers is higher among this group than among those producing the other substances and because fewer coagulase-negative staphylococci produced lysozyme than hemolysins or egg-yolk precipitation. Of 16 other species of bacteria and yeasts tested, all were found negative except Bacillus subtilis. Lysozyme production by staphylococci in heavily contaminated foods was not inhibited on plates containing sodium azide, whereas media containing 7.5% salt and sorbic acid were unsuitable. The possible relationship of lysozyme production to staphylococcal pathogenicity is discussed.